Egg development and hatching in two Red Sea damselfishes - He, Song; Berumen, Michael L. (Frontiers in Marine Science, 2023)
Damselfishes (family Pomacentridae) are widely distributed reef associated marine fishes. The family's diversity, iconic nesting behaviors, and high environmental adaptability contribute to the popularity of damselfishes as aquarium species, tourist attractions, and model scientific study organisms. In the present study, we conducted a series of in situ underwater observations on two Red Sea damselfishes: the Red Sea anemonefish (Amphiprion bicinctus) and the Maldives damselfish (Amblyglyphidodon indicus). We followed the egg development processes and provide an in-situ photo time series for both species. In our observations, some Amblyglyphidodon eggs began hatching as early as 120 hours post-spawning, whereas Amphiprion eggs never hatched until at least 144 hours post-spawning. Some of the key morphological and developmental features that could be indicative of developmental stage included eye structure and pigmentation/appearance, the proportion of the embryo to the yolk sack, spinal structures, and jaw/mouth structures. By referencing the time scale provided herein, in-situ observations could roughly indicate the developmental stage of the eggs in the nest and how much time is remaining before hatching. This would also help to decrease the underwater observation time of divers and minimize interference to nesting damselfishes but still enables the back-calculation of spawning times. The incorporation of this information with longer-term environmental data can provide important insight into factors driving reproductive cycles.